Private equity challenge: Vidrala as a glass packaging Lbo target - Rugeroni, Gonçalo Trigo Garcia (2021)
The goal of this thesis is to assess Vidrala as a potential leveraged buyout target. Market and company overviews were performedto evaluate the company ́s positioning and financial performance, as well as future trends within the glass packaging industry, the respective end-markets and other packaging solutions. This analysis was used to select the most suitable investment strategies and quantify the resulting business plan in financial terms. Finally, a valuation using several methods was conducted from which a capital structured was designed and potential returns calculated. This part will cover the Business Plan, the Valuation and the Capital Structure